STUDENT ROLE ADJUSTMENT IN ONLINE COMMUNITIES OF INQUIRY: MODEL AND INSTRUMENT VALIDATION - Garrison, Randy; Cleveland-Innes, Martha; Fung, Tak (Online Learning, 2004)
The purpose of this study is to validate an instrument to study role adjustment of students new to an online community of inquiry. The community of inquiry conceptual model for online learning was used to shape this research and identify the core elements and conditions associated with role adjustment to online learning (Garrison, Anderson and Archer, 2000). Through a factor analytic process it is shown that the instrument did reflect the theoretical model. It was also useful in refining the items for the questionnaire. The instrument is for use in future research designed to measure and understand student role adjustment in online learning.